Impact of Hydrogen on Carrier Mobility and Concentration in Graphene Decorated with Pd Nanoparticle. (28th July 2016) - Goto, Akihito; Takeuchi, Go; Yamachi, Ryosuke; Tanaka, Takahisa; Takahashi, Tsunaki; Uchida, Ken
Abstract : As a candidate of highly-sensitive hydrogen sensors, Palladium (Pd)-decorated graphene sensors have been investigated. Thanks to high reactivity of Pd nanoparticles to hydrogen and high surface-to-volume ratio of two-dimensionally layered graphene, graphene decorated with Pd nanoparticles can be used as a highly sensitive hydrogen sensor. Although the conductivity of Pd-graphene sensor is known to be greatly changed in hydrogen atmosphere, the mechanisms of conductivity change have not been fully understood. In this work, both carrier concentration and mobility in hydrogen are investigated using Hall effect measurement. It is shown that relative change of carrier concentration is greater when carrier concentration is lower. On the other hand, mobility is not systematically changed as a function of carrier concentration. This mobility behavior is attributed to the competition between greater effective mass and shorter screening length at higher carrier concentration. Based on these observations, we develop strategy for achieving high sensitivity in Pd graphene hydrogen sensor.